VERY LOW FREQUENCY ELECTROMAGNETIC SURVEY FOR SUBSURFACE CHARACTERIZATION WITHIN PART OF PHASE II, AHMADU BELLO UNIVERSITY, ZARIA, KADUNA STATE (FUDMA JOURNAL OF SCIENCES, 2023)
Lately, there has been an increase in the rate of structural failure in Nigeria and many parts of the world due to many reasons among which is subsurface inadequacy. This has led to loss of lives, properties, a lot of casualties and has become a critical problem that requires proper attention. Very low frequency (VLF) electromagnetic method was used for subsurface characterization within part of phase II, Ahmadu Bello University, Zaria, Kaduna State. VLF data were collected along fourteen (14) profiles covering an area of 84000m2 and measurements were made at 10m interval along each profile with profile length of 300m. The VLF data were collected using Terra-Plus VLF instrument and interpreted using KHFFILT software. The interpretation of VLF data using the Hjelt-Karous filter resulted in current density sections. The representative current density plots show the conductivity distribution of the subsurface. The current density variation was assumed to indicate the presence of fractures at the 14 stations of which profiles 7, 10 and 12 are not well fractured. The fractures identified are mostly oriented in the N-S direction of the study area
Keywords: Very Low Frequency, Terra-Plus VLF, Fracture zone, Current density